Correlates of Nonanemic Iron Deficiency in Restless Legs Syndrome - Zhu, Xiao-Ying; Wu, Ting-Ting; Wang, Hong-Ming; Li, Xuan; Ni, Ling-Yan; Chen, Tian-Jiao; Qiu, Meng-Yao; Shen, Jun; Liu, Te; Ondo, William G.; Wu, Yun-Cheng (Frontiers in Neurology, 2020)
Objective: Iron deficiency anemia (IDA) is a well-known cause of secondary restless legs syndrome (RLS). Iron deficiency without anemia (IDNA) is insidious, and its association with RLS is less evaluated. We investigate prevalence and features of IDNA in a consecutive cohort of patients with RLS. Methods: We included sequential RLS patients according to the IRLSSG criteria. IDNA is defined as serum ferritin <75μg/L with normal hemoglobin levels. RLS mimics and other comorbidities were carefully excluded. Results: 196 RLS patients without anemia and 26 RLS patients with IDA were included. 42.3% of RLS patients without anemia had iron deficiency. Women were much more susceptible for IDNA with a relative risk of 5.51 (95% CI 2.70–11.27, p<0.0001). Women IDNA RLS patients had younger age both at interview and at RLS onset compared to women RLS patients without iron deficiency (NID) (P<0.01). IDNA RLS patients were more likely to have severe/very severe tiredness or sleepiness during the day compared to NID RLS patients (P<0.05). Furthermore, IDNA RLS patients had longer duration of RLS (P<0.01 in men, P<0.05 in women) and younger age at onset (only in men, P<0.05) compared to IDA RLS patients. Conclusion: IDNA is frequent in RLS and iron deficient may be severe despite a normal hemoglobin level. Women are at much higher risk for IDNA, and IDNA in women presented some specific clinical features. Features of IDNA RLS are different from IDA RLS. Regular screening of peripheral iron parameters even in patients with normal blood counts is recommended for timely optimal management.